Peran Religiusitas Dalam Mengatasi Quarter Life Crisis Pada Mahasiswa: Systematic Literature Review - Nia Putri Cahyani; Alisyia Guspita; Azka Fauzan; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Quarter-Life Crisis (QLC) is a psychological phenomenon commonly experienced by individuals during emerging adulthood, characterized by anxiety, identity confusion, uncertainty about the future, and pressure in making life decisions. One factor believed to help individuals cope with QLC is religiosity. This study aims to systematically examine the role of religiosity in helping university students navigate Quarter-Life Crisis. The method used is a Systematic Literature Review (SLR) with a qualitative descriptive approach. Articles were searched through electronic databases using the keywords religiosity, quarter-life crisis, and university students. Out of 281 documents retrieved, 6 articles met the inclusion criteria and were further analyzed. The findings indicate that religiosity functions as a protective factor that can help reduce the level of QLC by enhancing meaning in life, inner peace, self-acceptance, resilience, and more adaptive coping strategies. However, the effectiveness of religiosity does not operate in isolation, as it is also influenced by other factors such as self-efficacy, social support, and tolerance of uncertainty. These findings suggest that addressing QLC among university students requires a holistic approach that simultaneously considers spiritual, psychological, and social aspects.